PENGARUH DIAMETER PULLY ALTERNATOR DALAM PENGISIAN BATERAI PADA KENDARAAN RODA EMPAT - RESEP SEMBIRING (JURNAL ILMIAH KOHESI, 2020)
The study was conducted by varying pully diameters of 70, 73, 82 mm where all three variations of this diameter were testedthree times each. Testing was conducted on rounds of 1000, 1900 and 2500 rpm engines. And in conclusion the researchersstated that there is an effect of the increase in the rotation of the machine and the pully diameter of the alternator on theoutput voltage of the alternator but has no effect on the output current of the alternator, at each turn and at any pullydiameter size there is no significant effect on the slow or rapid charging of the batrai. Slow or fast charging of the batterydepends heavily on the size of the current used and usually the large current used is 10% of the battery capacity charged.